2020
DOI: 10.1017/s0954422419000258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity on cholesterol metabolism and its implications for healthy ageing

Abstract: The last few decades have witnessed a global rise in the number of older individuals. Despite this demographic shift, morbidity within this population group is high. Many factors influence healthspan; however, an obesity pandemic is emerging as a significant determinant of older people’s health. It is well established that obesity adversely affects several metabolic systems. However, due to its close association with overall cardiometabolic health, the impact that obesity has on cholesterol metabolism needs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 209 publications
(206 reference statements)
1
20
0
7
Order By: Relevance
“…Previous studies have shown a clear association between an increased body weight, obesity, and a higher synthesis of cholesterol [28]. Additionally, in the present study, the concentration of liver cholesterol was considerably increased in the obese rats, clearly showing that hemp seed oil and, to a lesser extent, poppy seed oil, lowered the concentration of liver cholesterol.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown a clear association between an increased body weight, obesity, and a higher synthesis of cholesterol [28]. Additionally, in the present study, the concentration of liver cholesterol was considerably increased in the obese rats, clearly showing that hemp seed oil and, to a lesser extent, poppy seed oil, lowered the concentration of liver cholesterol.…”
Section: Discussionsupporting
confidence: 76%
“…Because statins do not have a posthepatic circulation of very high concentrations, it is unlikely that they have systemic effects on tissues/tumors, making their own cholesterol/27-HC. In addition to de novo biosynthesis, intracellular cholesterol is also supplemented from the diet, particularly in patients with obesity ( 35 ). Therefore, blocking de novo cholesterol biosynthesis alone is unlikely sufficient to reduce 27-HC in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find any differences in lipids including NEFA, LDL, HDL, TG, except TC among groups at 8 weeks postpartum, which agreed with the previous studies 19 , 25 . However, TC levels were significantly higher in the HFHS/OP than the CON suggesting that obesity status may influence cholesterol metabolism 26 , 27 . Further, we did not find any differences in resistin and leptin at 8 weeks postpartum, which are typically altered with obesity and T2DM 19 , 28 .…”
Section: Discussionmentioning
confidence: 90%